Forming A System of Inclusive Education: The Interaction of Government and Universities - Ellana MOLCHANOVA; Yuliia HOLOVNIA; Kateryna KOVTONIUK; Olha DIACHENKO (Communications of International Proceedings, 2023)
The basis of the article is the system of any organizational structure or formation adapted to an effective educational system. Our research aimed at identifying an adaptive system: inclusive education is a subsystem in the system of higher education. In Ukraine, the number of children who are classified as children with special educational needs is growing. However, in our country, as well as in EU countries, legal regulation is limited to children from 2 to 18 years. Therefore, school graduates do not have the will to get a higher education. Due to the lack of regulation or promotion of inclusive education at the university level, we propose an actor approach to the formation of the system of inclusive education. The article analysed the system and its structure, identified elements, criteria and sub-criteria, and revealed their interaction. A model of interaction between authorities and universities with the aim of forming a system of inclusive education at the level of HEI is proposed.
Keywords: Inclusive Education; Educational System; Educational Institutions; Adaptive System